Entamoeba histolytica antigen-specific induction of human immunodeficiency virus replication. - Croxson, S (1988)
Replication of human immunodeficiency virus (HIV) may be initiated in infected lymphocytes by antigenic or mitogenic stimulation. A soluble protein derived from an invasive strain of Entamoeba histolytica (amoebic antigen [AA]) was used to study the lymphoblastic responses of T lymphocytes derived from 8 HIV-seronegative homosexual men (controls) and 15 HIV-seropositive homosexual men (patients). The soluble protein was also used in long-term cultures as a stimulus for HIV replication. No control or patient produced detectable lymphoblastic responses to AA in a 6-day tritiated-thymidine incorporation assay. Of 15 patients, 5 (33%) produced HIV p24 (ranging from 31 pg/ml to 151 ng/ml) in response to AA in 30-day cell cultures. HIV p24 was expressed in three of seven patients in response to AA but not to the T-lymphocyte mitogen phytohemagglutinin. Implications for managing HIV-infected patients are discussed.